2020
DOI: 10.1177/2324709620966475
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Aspergillosis “Fungal Balls” Complicating COVID-19

Abstract: Severe acute respiratory syndrome coronavirus-2 infection (SARS-CoV-2), commonly known as COVID-19 (coronavirus disease-2019), began in the Wuhan District of Hubei Province, China. It is regarded as one of the worst pandemics, which has consumed both human lives and the world economy. COVID-19 infection mainly affects the lungs triggering severe hypoxemic respiratory failure, also providing a nidus for superimposed bacterial and fungal infections. We report the case of a 73-year-old male who presented with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
(10 reference statements)
0
22
0
4
Order By: Relevance
“…1A) are other important infections in this context. 3,4 Tadolini et al 4 reported the detection of cavitary lesions in23 (47%) of 49 patients with current or former tuberculosis and COVID-19.…”
Section: To the Editormentioning
confidence: 99%
“…1A) are other important infections in this context. 3,4 Tadolini et al 4 reported the detection of cavitary lesions in23 (47%) of 49 patients with current or former tuberculosis and COVID-19.…”
Section: To the Editormentioning
confidence: 99%
“…A. niger , A. terreus , A. lentulus , A. nidulans , A. awamori , A. penicillioides , and A. citrinoterreus [ 23 , 56 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. The most used diagnostic methods were cultivation, galactomannan and (1,3)-β-D-glucan detection, MALDI-TOF, histopathology, serological tests, PCR, and sequencing [ 23 , 56 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , …”
Section: Aspergillosis and Covid-19mentioning
confidence: 99%
“…It should be noted that in some of the A. fumigatus isolates, the TR34/L98H mutation in the Cyp51A gene was detected, which is associated with environmental azole resistance to antifungal agents [ 78 , 83 ]. Caspofungin, voriconazole, amphotericin B, anidulafungin, posaconazole, itraconazole, fluconazole or isavuconazole were used in antifungal treatment [ 23 , 56 , 62 , 63 , 64 , 66 , 67 , 69 , 70 , 71 , 72 , 74 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Aspergillosis and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations